Plan for The Efficient Use and Saving of Water at The Universidad del Norte - Adolfo Meise; Alma Lucia Diazgranados; Oscar Álvarez González; Daniel Rincón; Jeniffer Ariza Reino; Cristian Loaiza (Journal of Sustainability Perspectives, 2021)
Portable water is an essential resource for living, currently there is enough water in the world for this, but its distribution is not adequate in different places or at different seasons of the year. Climatic variations affect the water supply capacity generate economic, social and environmental problems. The commitment of Universidad Del Norte with the environment and its transversally in its missionary functions of teaching, research, and extension crystallize in academic and administrative strategies, complying not only with environmental legislation, but also management with criteria of resource efficiency (Water, energy, air, waste, fauna and flora) promoting environmental education, conservation, respect for nature and long-term sustainability. The foregoing derives from the responsibility that Universidad Del Norte has had with the community in creating a PUEAA - Plan for the efficient use and saving of water, which describes the strategies aimed at the conservation and use of water resources. The following article describes the strategies that the Universidad Del Norte carries out to have a continuous supply of water, guarantee the quality of drinking water for its consumption processes, treat all wastewater resulting from its processes, and finally reuse all water that is finally use in campus gardens.